Freezing of rabbit semen after the addition of glycerol and dimethylsulfoxide in the extender - SAMOUILIDIS (Σ. ΣΑΜΟΥΗΛΙΔΗΣ) S.; SAOULIDIS (Κ. ΣΑΟΥΛΙΔΗΣ) K.; FOUKOS (Α. ΦΟΥΚΟΣ) A.; YPSILANTIS (Π. ΥΨΗΛΑΝΤΗΣ) P.; DEMERTZIS (Α. ΔΕΜΕΡΤΖΗΣ) A.; SBIRAKI (Α.Π. ΣΜΠΙΡΑΚΗ) A. P. (Journal of the Hellenic Veterinary Medical Society, 2018)
In this study, semen from 10 rabbits was frozen after it was diluted in two different extenders, A and B. Extender A consisted of Tris-buffer in which 20% of egg yolk and 3% of glycerol were added, while extender Β had the same composition, plus 3% of dimethylsulfoxide (DMSO). The semen of the buck exhibiting the best post-thaw motility in the two extenders, was used for the insemination of two corresponding groups (I and II) of 20 does each. The average sperm motility of fresh semen (77%) was significantly reduced (P<0.05) after it was frozen in the extender A (47%) and Β (54%). The post-thaw sperm motility in extender Β was significantly higher (P<0.05) than that in extender A. The percentage of the animals that gave birth in group II (60%) was increased compared to that of the animals in group I (50%), but not significantly (P>0.05). Also, no significant difference (P>0.05) was observed between the average litter size of group I (6,8±1,7) and group II (7,0±1,9). Thereafter, it is concluded that freezing rabbit semen in an extender that contains a combination of the cryoprotective agents glycerol and DMSO, in the proportion of 3% and 3%, respectively, results in a significant improvement of post-thaw sperm motility, while it doesn’t affect significantly its fertility value neither the size of the litters.